2019
DOI: 10.1007/s00289-019-02789-w
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic talc as catalyst and filler for waterborne polyurethane-based nanocomposite synthesis

Abstract: In this work, synthetic talc was used as catalyst and filler aiming to obtain waterborne polyurethane (WPU) nanocomposites by in situ polymerization. Filler was used both in gel and in powder forms in order to compare its effects into the WPU matrix. The use of synthetic talc as filler is interesting due to the possibility of hydrogen bond formation between WPU chains/Si-O-Si and OH groups in synthetic talc edges promoting changes in physical, mechanical and thermal properties. Moreover, WPUs are environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…This is another clear indication of the presence of an inorganic filler in the polymer blend structure. The combined XRD and TEM results found for neat INZEA were in agreement with those recently reported by Dias et al [55], who did not observe a good dispersion and just some homogeneous distribution of the inorganic filler in polyurethane-based nanocomposites. These authors also reported that talc tactoids in these formulations were around 500 nm wide, which are similar to the results obtained in this study.…”
Section: Thermal Stabilitysupporting
confidence: 92%
“…This is another clear indication of the presence of an inorganic filler in the polymer blend structure. The combined XRD and TEM results found for neat INZEA were in agreement with those recently reported by Dias et al [55], who did not observe a good dispersion and just some homogeneous distribution of the inorganic filler in polyurethane-based nanocomposites. These authors also reported that talc tactoids in these formulations were around 500 nm wide, which are similar to the results obtained in this study.…”
Section: Thermal Stabilitysupporting
confidence: 92%
“…The reactants ratio used in synthetic talc synthesis were based on the chemical formula of natural talc (Mg 3 Si 4 O 10 (OH) 2 ). When using different metals the reactants are mixed in stoichiometric proportions based on the chemical formula: (Si 4 (Mg x Ni 1−x ) 3 O 10 (OH) 2 with 0 < x < 1, Si/Mg-Ni = 4/3) [44,45]. In order to synthesize the talc-Ni, the substitutions of magnesium by nickel were performed from 25 to 100%, as shown in Table 1.…”
Section: Synthetic Talc Synthesismentioning
confidence: 99%
“…Waterborne polyurethane (WPU) is a binary gel system with water as the dispersed phase, which has the advantages of no pollution, safety, reliability, excellent mechanical properties, good compatibility, good film formation, easy modification, and so forth. Its volatility is low, and pollution can be avoided when used, which is beneficial to human health 1 . WPU also retains the characteristics of polyurethane (PU) such as high strength and impact resistance.…”
Section: Introductionmentioning
confidence: 99%